Surface Interaction of Proteins - Pukar Vidyarthi, Ram (Asian Journal of Chemistry, 2010)
Proteins contain a lot of hydrogen bonds. The rupture of these hydrogen bonds are responsible for the helix coil transition in protein leading to the conformational changes having a little variation of pH and ionic strength. But the situation is different both in solid state and in the atmosphere of various percentages of water vapour. Surface interaction of ammonia gas on casein and ovalbumin has been found to be facilitated by the adsorption of moisture on these proteins. The ± interaction and proton transfer on the surface of solid proteins seem to be easier with moist molecules. Some conformational changes also occur due to the exchange of hydrogen bond between ammonia and amide linkages in protein chain. The exchanging capacity decreased considerably in ammonia than in the vapour of alcohol.